2005
DOI: 10.1097/01.sap.0000168246.75891.62
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Recipient Sites in Fat-Graft Survival

Abstract: The survival of fat grafts depends on many factors, 1 of the major being early revascularization. Early studies showed that adipose tissue has a low tolerance to ischemia. Some methods have been described to increase the tolerance of adipose tissue to ischemia. This study was designed to compare volume maintenance of the transplanted fat graft in different recipient sites of the rabbit face. Three groups of 5 New Zealand white rabbits were studied. Fat grafts harvested from the right inguinal fat pad were tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 30 publications
2
41
0
1
Order By: Relevance
“…Fat graft volume reduction appears to be caused, in part, by mechanical stresses from harvesting techniques [3] and early ischemia-reperfusion injury [4]. These injuries can lead to apoptosis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Fat graft volume reduction appears to be caused, in part, by mechanical stresses from harvesting techniques [3] and early ischemia-reperfusion injury [4]. These injuries can lead to apoptosis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using small animals have evaluated the viability of AFG and suggested different technical aspects to obtain better integration 19,20,22 . Karacaoglu et al 20 analyzed the AFG volume maintenance in different recipient sites in a rabbit model.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Karacaoglu et al 20 analyzed the AFG volume maintenance in different recipient sites in a rabbit model. Based on histopathologic analyses, the authors observed a significant increase of fat graft survival in supramuscular layer (81.95%) than in submuscular layer (37.31%) (P<0.05).…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant aspect of adipose tissue engineering is to reduce the fat absorption and to retain its predesigned physical contour and dimension after transplantation (Karacaoglu et al 2005;Yamaguchi et al 2005;Coleman and Saboeiro 2007;Missana et al 2007;Ogawa et al 2007). Yoshimura and co-workers recently demonstrated that adipose derived stem or stromal cells (ADSCs)-enriched AFT was efficient in breast augmentation and facial lipoatrophy, with stable natural contour and without any major side effects (Yoshimura et al 2008a, b).…”
Section: Introductionmentioning
confidence: 99%